Dietary selenium intake and the risk of kidney stones in adults, an analysis of 2007–2018 National Health and Nutrition Examination Survey, a cross-sectional study - Liu, Minghui; Cui, Zhongxiao; Chen, Jinbo; Gao, Meng; Zhu, Zewu; Chen, Hequn (Frontiers in Nutrition, 2022)
Purpose To evaluate the association between dietary selenium intake and the risk of kidney stones in adults. Methods We performed a cross-sectional analysis using data from 2007-2018 National Health and Nutrition Examination Survey (NHANES). Dietary intake information of 30,184 participants was obtained using first 24-h dietary recall interview, and kidney stones were presented by a standard questionnaire. The quartile analysis, stratified analysis and nonlinearity analysis were used to estimate the association between dietary selenium intake and kidney stones after an adjustment for potential confounders. Results The multiple logistic regression indicated that the fourth quantile (Q4) of dietary selenium intake had a significantly lower risk of kidney stones than the first quantile (Q1) in Model 3 (OR 0.82, 95% CI 0.70-0.97, P = 0.022). The stratified analyses indicated there were significant statistical differences between dietary selenium intake and kidney stones among younger (age<50) (OR 0.69, 95% CI 0.53-0.90, P = 0.006), male (OR 0.76, 95% CI 0.61-0.95, P = 0.015) and overweight/obese (BMI≥25.0) (OR 0.78, 95% CI 0.65-0.94, P = 0.008) individuals in Model 3. Conclusions Our study revealed that dietary selenium intake is adversely associated with the risk of kidney stones for the US population, especially for younger (age<50), male and overweight/obese (BMI≥25.0) individuals. Further studies are required to confirm our findings and clarified the biological mechanisms.